Programming Arduino : getting started with Sketches - Monk, Simon (McGraw-Hill, 2016)
"This thoroughly updated guide shows, step-by-step, how to quickly program all Arduino models--including the Arduino Uno R3. Written by hobbyist and electronics guru Simon Monk, Programming Arduino: Getting Started with Sketches, Second Edition, features easy-to-follow explanations, fun examples, and downloadable sample programs. Discover how to write basic sketches, use Arduino's modified C language, store data, and interface with the Web. You will also get hands-on coverage of C++, library writing, and programming Arduino for the Internet of Things."--provided by Amazon.com.